Relationship Between the Choice of Clinical Treatment, Gait Functionality and Kinetics in Patients With Comparable Knee Osteoarthritis - Tassani, Simone; Tio, Laura; Castro-Domínguez, Francisco; Monfort, Jordi; Monllau, Juan Carlos; González Ballester, Miguel Angel; Noailly, Jérôme (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: The objective of this study was to investigate the relationship between the choice of clinical treatment, gait functionality, and kinetics in patients with comparable knee osteoarthritis. Design: This was an observational case-control study. Setting: The study was conducted in a university biomechanics laboratory. Participants: Knee osteoarthritis patients were stratified into the following groups: clinical treatment (conservative/total knee replacement (TKR) planned), sex (male/female), age (60–67/68–75), and body mass index (BMI) (<30/≥30). All patients had a Kellgren–Lawrence score of 2 or 3 (N = 87). Main Outcome Measures: All patients underwent gait analysis, and two groups of dependent variables were extracted: • Spatiotemporal gait variables: gait velocity, stride time, and double-support time, which are as-sociated with patient functionality • Kinetic gait variables: vertical, anterior–posterior, and mediolateral ground reaction forces, ver-tical free moment, joint forces, and moments at the ankle, knee, and hip Multifactorial and multivariate analyses of variance were performed. Results: Functionality relates to treatment decisions, with patients in the conservative group walking 25% faster and spending 24% less time in the double-support phase. However, these differences vary with age and are reduced in older subjects. Patients who planned to undergo TKR did not present higher knee forces, and different joint moments between clinical treatments depended on the age and BMI of the subjects. Conclusions: Knee osteoarthritis is a multifactorial disease, with age and BMI being confounding factors. The differences in gait between the two groups were mitigated by confounding factors and risk factors, such as being a woman, elderly, and obese, reducing the variability of the gait compression loads. These factors should always be considered in gait studies of patients with knee osteoarthritis to control for confounding effects.